Implementasi Flutter Dalam Pengembangan Aplikasi Pemesanan Sangkar Burung Berbasis Android - Andri Kurnia Maulana; Nizirwan Anwar; Binastya Anggara Sekti (Ikatan Ahli Informatika Indonesia, 2023)
In recent years, mobile technology, including the field of electronic commerce, has seen rapid growth. Bird cages have become one of the most sought-after products in the bird trading industry. However, there are several issues to consider during the ordering process, which often consume time and effort. The objective of this research is to create and develop an Android-based bird cage ordering application with a user-friendly interface that allows people to quickly and easily select and purchase bird cages. The research methodology involves identifying the requirements for aspects such as material, size, bird cage design, and shipping information. Flutter enables user interface designers to display a list of bird cages with photos and details, as well as customization options. Firebase provides backend storage for storing history, authentication, and orders. The application features include registration, login, searching for bird cages, viewing details with images, ordering, tracking orders, and logging out. By offering a variety of bird cage options, this application streamlines the bird cage ordering process. Customers can monitor the status of their orders and easily choose the most suitable one. Flutter simplifies cross-platform development. Using the Flutter framework and Firebase as the backend, users can select and order bird cages according to customer or application user needs.